A phase 2 study of Rituximab‐Bendamustine and Rituximab‐Cytarabine for transplant‐eligible patients with mantle cell lymphoma. (5th January 2016) - Armand, Philippe; Redd, Robert; Bsat, Jad; Mayuram, Sangeetha; Giardino, Angela; Fisher, David C.; LaCasce, Ann S.; Jacobson, Caron; Davids, Matthew S.; Brown, Jennifer R.; Weng, Li; Wilkins, Jennifer; et al.
Summary: Chemoimmunotherapy followed by autologous stem cell transplantation (ASCT) is a standard therapy for transplant‐eligible patients with newly diagnosed mantle cell lymphoma (MCL). The achievement of complete remission (CR) and minimal residual disease (MRD) negativity are associated with better outcomes. We tested an induction regimen of rituximab/bendamustine followed by rituximab/high‐dose cytarabine (RB/RC). This phase 2 study (NCT01661881) enrolled 23 transplant‐eligible patients aged 42–69, of whom 70% were MCL international prognostic index low‐risk. Patients received three cycles of RB followed by three cycles of RC. The primary endpoint of the trial was the rate of CR after six cycles of therapy, with a rate of 75% considered promising. 96% of patients achieved a CR/unconfirmed CR after treatment, meeting the primary objective. One patient progressed on study, one declined ASCT in CR, and the remaining 21 underwent successful stem cell collection and ASCT. After a median follow‐up of 13 months, the progression‐free survival rate was 96%. Among 15 MRD‐ evaluable patients who completed treatment, 93% achieved MRD negativity after RB/RC. In conclusion, RB/RC achieves very high CR and MRD negativity rates in transplant‐eligible patients, with a favourable safety profile. RB/RC warrants further comparative studies, and may become a useful alternative to RCHOP (rituximab, cyclophosphamide, doxorubicin, vincristine, prednisone)‐based induction regimens in this patient population.